(untitled) (Research, Society and Development, 2021)
Family farming is a complex structure and plays a key role in socioeconomic and environmental settings worldwide, yet most farmers are subject to public neglect and many risk factors. This study aims to analyze and debate issues about the risks of pesticide use, especially in family farming. To carry out the research, the integrative review methodology was applied, which provides ample information about a subject/problem, interweaving the conceptual basis with the latest developments. The results showed that family farmers are more vulnerable to the damage caused by pesticides than other rural groups. Some of these social actors are unaware of the damage that these products can cause or do not have adequate equipment to protect themselves. The highest exposures to these risks are found in developing countries. The annual poisoning notifications cannot be considered absolute numbers, because many cases happen in regions with difficult access to information. It is considered that for a change in the panorama, it is necessary to support other styles of more alternative agriculture, making the functioning of agro-ecosystems more resilient and ecological, that the responsible entities have measures based on more integrated approaches, which consider the socioeconomic, environmental and health context in which they are inserted, as well as promote information for the field, aiming at the quality of life of individuals, so important to society.